Effect of curing temperature freeze-thaw failure mechanism and damage model of equal-strength air-entrained concrete. - YongHe Liu; Bo Yang; Aojun Guo (PLoS ONE)
The Belt and Road strategy has significantly advanced the scale of infrastructure construction in the Qinghai-Tibet Plateau permafrost area. Consequently, this demands higher requirements on the strength and frost resistance of concrete (FRC) cured under low-temperature and negative-temperature conditions. Accordingly, in this study, tests on the mechanical properties and FRC were conducted under standard curing, 5 °C curing, and -3 °C curing conditions. The pore structure characteristics of concrete subjected to freeze-thaw (F-T) damage (FTD) under different curing methods were analyzed using nuclear magnetic resonance. The study results show that when the air content is constant, the compressive strength of concrete (CSC) tends to decrease with the curing temperature. Moreover, the occurrence of an age lag phenomenon is evident. The compressive strength of concrete cured under standard curing for 28-d was comparable to that achieved by concrete cured at 5 °C curing for 56-d and at -3 °C curing for 84-d. Under the same curing conditions, the CSC decreases with increasing air content. Observations revealed that with the air content in the concrete set at 0.08%, the material's compressive strength was at its minimum. As the number of F-T cycles increases, the concrete transverse relaxation time (T2) curve shifts to the right, and the proportion of both harmful and multi-harmful pores increases. Based on the same CSC under different curing methods, the FRC under 5 °C curing and -3 °C curing conditions is considerably lower than that under standard curing conditions. Moreover, the FRC exhibits an increasing and then a decreasing trend with increasing air content. Concrete exhibits the best frost resistance when the air content is 3.6%. It was established that an optimal range exists for air content in concrete. If the air content is too low, there is only a slight improvement in the FRC. Conversely, if the air content was excessively high, it leads to a significant decrease in frost resistance. Further, this study establishes an FTD model for concrete under 5 °C curing and -3 °C curing conditions considering the compressive strength factors of concrete under standard curing conditions for 28-d. This study is anticipated to be used as reference for determining the FRC cured under different temperatures.